2016
DOI: 10.1128/jcm.01160-16
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Brief Case: Neonatal Meningitis Caused by Listeria monocytogenes Diagnosed by Multiplex Molecular Panel

Abstract: Answer: c. Listeria species are intrinsically resistant to several classes of antibiotics, including broad-spectrum cephalosporins, first-generation quinolones, fosfomycin, and monobactams. Recognizing the intrinsic resistance to broad-spectrum cephalosporins is clinically important, as they are commonly employed to empirically treat sepsis and meningitis of unknown etiology. The mechanism associated with cephalosporin resistance in Listeria spp. is complex and is thought to be secondary to unique penicillin b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 7 publications
5
3
5
Order By: Relevance
“…Conventional assays confirmed presence of VZV and H. influenzae, whereas HHV-6 was not found by specific PCR Using this selection criteria we selected 171/4623 CSF specimens for additional syndromic molecular testing. Overall we observed positive results in 56/171 (32%), which is higher than in other published studies [6,7,[9][10][11][12][34][35][36][37][38] and substantially higher compared to the multicenter evaluation study [6] and three other studies [7,32,33], that reported positivity rates of under 15% (p < 0.0001). In addition, we could increase the amount of bacterial pathogens to 53% of the specimens, again this is more than in other published studies that observed positive ranges for bacterial pathogens between 15 and 37% [6,7,32,33].…”
Section: Discussioncontrasting
confidence: 65%
“…Conventional assays confirmed presence of VZV and H. influenzae, whereas HHV-6 was not found by specific PCR Using this selection criteria we selected 171/4623 CSF specimens for additional syndromic molecular testing. Overall we observed positive results in 56/171 (32%), which is higher than in other published studies [6,7,[9][10][11][12][34][35][36][37][38] and substantially higher compared to the multicenter evaluation study [6] and three other studies [7,32,33], that reported positivity rates of under 15% (p < 0.0001). In addition, we could increase the amount of bacterial pathogens to 53% of the specimens, again this is more than in other published studies that observed positive ranges for bacterial pathogens between 15 and 37% [6,7,32,33].…”
Section: Discussioncontrasting
confidence: 65%
“…In addition, we could increase the amount of bacterial pathogens to 53% of the specimens, again this is more than in other published studies that observed positive ranges for bacterial pathogens between 15-37% [6,7,32,33]. Indeed, bacteria were the most abundant In concordance with other studies [6,7,[9][10][11][12][34][35][36][37][38], S. pneumoniae (17/30) In four samples, potentially false positive results of FilmArray ME panel occurred, including three samples tested positive for bacterial pathogens by multiplex PCR that remained culture negative.…”
Section: Discussionsupporting
confidence: 88%
“…Using this selection criteria we selected 171/4623 CSF specimens for additional syndromic molecular testing. Overall we observed positive results in 56/171 (32%), which is higher than in other published studies [6,7,[9][10][11][12][34][35][36][37][38] and substantially higher compared to the multicenter evaluation study [6] and three other studies [7,32,33], that reported positivity rates of under 15% (p<0.0001). In addition, we could increase the amount of bacterial pathogens to 53% of the specimens, again this is more than in other published studies that observed positive ranges for bacterial pathogens between 15-37% [6,7,32,33].…”
Section: Discussioncontrasting
confidence: 65%
“…Patients who were positive for respiratory viruses were also less likely to be discharged with oral antimicrobial therapy (26). We previously described two cases in which rapid diagnosis of bacterial meningitis, attributable to Listeria monocytogenes and Haemophilus influenzae, with a molecular panel assay allowed definitive diagnosis and optimization of antimicrobial therapy (27)(28)(29). In this study, the availability of the HSV PCR results on a 24-h/7-day basis resulted in a significant reduction in the duration of acyclovir treatment in the postimplementation arm.…”
Section: Discussionmentioning
confidence: 78%